Merger And Innovation To Improve Organization’s Performance In Indonesia To Fight Industrial Revolution 4.0: Case Study Merger Bank BTPN - Diana Tambunan; Sugeng Wahyudi; Harjum Muharam (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2021)
An organization will conduct a merger strategy with companies that have strong technology to overcome the challenges of industrial transformation 4.0. In 2018 Bank BTPN merged with SMBCI with the hope of strengthening banking technology so that it could serve customers of various segments with various services throughout Indonesia.This research is a case study conducted at Bank BTPN which contributes to prove whether with merger, Bank BTPN's financial performance has improved. The method used is ratio analysis by comparing the financial performance of Bank BTPN before merger and after merger and the data obtained from the 2019 Annual Report and published financial statement 2020. The results showed that the merger strategy made Bank BTPN able to use assets, funding, and technology owned by SCMBI in innovating the digital banking business of Jenius banking products, BTPN Wow! and other banking products so that the post merger of Bank BTPN's financial performance has increased rapidly both in terms of assets to be the ninth largest in Indonesia, as well as 41% increase in net profit to Rp 2.9 trillion in 2019. This research proposes the concept of business model where merged bank should take five actions: 1) Innovation Business Digital Bangking, (2) Expansion of Customer Segmentation, (3) Diversification of Products/Market, (4) Quality of Human Resources, (5)Corporate Governance.